Changes in Working Women’s Self-Reported Subjective Wellbeing and Quality of Interpersonal Relationships During COVID-19: A Quantitative Comparison of Essential and Non-essential Workers in Singapore - Tan Poh Lin (Cambridge University Press, 2023)
10.1017/S0047279423000016